Invasive endometrial adenocarcinoma and missed abortion: A case report - Nicole B. Gaulin; Lakshmi Harinath; Sharon Liang; Thomas C. Krivak; Eirwen M. Miller (Elsevier, 2020)
Background: Endometrial cancer is the most common gynecologic cancer in the United States; however, reports of endometrial cancer diagnosed in the setting of intrauterine gestation are rare. Case: We describe the case of a clinical stage IA grade 1 endometrioid endometrial adenocarcinoma diagnosed at the time of D&C performed for missed abortion in a gravida 1 para 0 female with no identifiable risk factors. Fertility-sparing treatment, with combined oral megestrol acetate and levonorgestrel intrauterine system, was used to manage this incidentally-diagnosed carcinoma with endometrial sampling every 3 months. Keywords: Endometrial cancer, Missed abortion, Spontaneous abortion, Intrauterine progestin, Fertility sparing treatment